Chondrosarcoma in the Petrous Apex: Case Report and Review - Banaz, F.; Edem, I.; Moldovan, I. D.; Kilty, S.; Jansen, G.; Alkherayf, F. (Journal of Neurological Surgery Reports, 2018)
Introduction Surgical treatment of petrous apex chondrosarcoma is challenging due to the location of the tumor. Using an endoscopic technique for tumor resection is favored since it provides a minimally invasive approach.Case Presentation A 57 years old female was admitted for acute onset of left abducens nerve palsy and occasional headache mainly on the left side of the retro-orbital area with some radiation to the left occiput. Magnetic resonance imaging (MRI) and computed tomography (CT), at the time of admission, were showed lytic lesion on the left petrous apex and left part of the clivus. Results of metastatic workup were negative. The surgical procedure considered was expanded endoscopic endonasal transclival approach to the left of the petrous apex and reconstruction with a pedicled nasoseptal flap with image guidance system. The pathology confirmed chondrosarcoma on myxoid background. The surgical procedure was uncomplicated. The abducens nerve palsy was resolved in few weeks and no new deficits occurred. Postoperative MRI showed complete resection of the tumor.Conclusion Expanded endoscopic endonasal transclival approach to petrous apex and reconstruction appears to be safe and feasible technique, capable of achieving total removal of identified lesions near the petrous apex. Nonetheless, future studies with a greater number of patients are crucial to confirm and consolidate this initial impression.
Keywords: chondrosarcoma; endonasal resection; endoscopic resection; skull base tumors; petroclival; case report; review